Patient and health provider factors affecting diagnostic delays of pulmonary tuberculosis in Jabalpur district of Madhya Pradesh, India: a cross-sectional study - Sahu, Rupesh; Verma, Prashant; Kasar, Pradeep K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Delay in diagnosis of pulmonary tuberculosis (PTB) causes patients to have more severe disease, more complications and lead to higher mortality with disease spread. The aim of the study was to estimate patient proportion having delayed diagnosis of PTB and to estimate patient’ and health providers’ delay and associated factors. Methods: This cross sectional study was conducted on sample of 135 new sputum positive PTB patients from nine designated microscopy centres of Jabalpur district. Data collected on modified world health organization questionnaire. The criterion for defining delay was formulated keeping in mind the Revised TB Control Programme algorithm for diagnosis of PTB in PTB suspects. Mann Whitney U and Kruskal Wallis tests were used (α=5%). Results: Mean age was 33.87 (14.3) years. Males constituted 66.7%. Proportion of diagnostic delay was 87.4%. Median patient and health care personnel (HCP) interval were 39 days (IQR 22-75) and 34 days (IQR 12-79) respectively. Factors significantly associated with patient delay were poor knowledge about TB, smoking, symptoms perceived non serious, first action with symptom onset, and mode of transport patient used to reach the nearest public health facility. Stigma didn’t affected patient interval. Factors significantly associated with health providers’ delay were first consultations with; a non-formal HCP, private health facility, non-allopathic practitioner; consultation with multiple HCP’s; living more than half an hour away from public health facility. Conclusions: Unacceptable high delay in diagnosis, more from patient side. More attempts at increasing awareness are needed.